Some note’s from Farabi ‘s work el-adab el-mulukyye ve al-ahlak el ihtiyariyye (Journal of Oriental Studies, 2020)
Al-Farabi, known as Muallim-i Sani after Aristotle, is the founder of Islamic philosophy because of his works in the field of logic in the Islamic world as well as in the Turkish world. Although he is busy with all the sciences from theology to metaphysics, from philosophy to logic, from moral to politics, from physics to astronomy, and from psychology to music, Al-Farabi was mostly interested in philosophy, metaphysics, physics, morality and politics and he wrote more than 100 works large and small in Arabic; today only half of these works have reached to us. So we need to study and detailed research on these works. Al-Farabi obtained the logic and philosophy from Aristotle and the moral and political philosophy from the Platon. However, as in logic and philosophy, he made a new breakthrough in the moral and political philosophy by adding the thought of Islam and its own aesthetics and so, he is considered the founder of Islamic philosophy. In this online symposium, we will discuss his work at this article named “Siyase el-Mulukiyye” on the moral philosophy that is attributed to al-Farabi through Eflatun. Key words: al-Farabi, philosophy, manuscript, virtuous city, civil policy, the path of happiness.